Real Time Sales Data Visualization at Agung Wastra Using Looker Studio - Sandhiyasa, I Made Subrata; Parniti, I Gusti Agung Ayu Pira; Wijaya, Bagus Kusuma; Suandana, Ni Putu Widantari (TECHNOVATE: Journal of Information Technology and Strategic Innovation Management, 2025)
Agung Wastra is a company that opertes in the field of facilities and infrastructure for Hindu religious ceremony activities. The company uses Microsoft Excel in processing sales data. The weakness of the data or information produced is that it is still in table form and does not display more interactive information in graphic form, making it difficult for companies in a short time. Therefore, this research aims to build a sales data visualization system using looker studio. This visualization helps companies process table data into information in the form of graphs so that it doesn't take a long time to see the company's sales development. The research method used in this research is Kimball's nine steps method. This research goes through the stages of company data analysis, data warehouse design, extract transform load process, implementation of data visualization, and system testing. This system was tested using the user acceptance test method and obtained results with a percentage of 92.5% or strongly agree, which means that the sales data visualization is in accordance with the needs of the agung wastra company. The results of this research are seven pages displaying company information in the form of graphics to assist in decision making.